2017
DOI: 10.15171/ijb.1608
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Electric Current Generation Potential of the Pseudomonas aeruginosa Using Glucose, Fructose, and Sucrose in Double Chamber Microbial Fuel Cell

Abstract: Different concentrations of the simple carbon substrates i.e. glucose, fructose, and sucrose were tested to enhance the performance of the mediator-less double chamber microbial fuel cell (MFC). The power generation potential of the different electron donors was studied using a mesophilic Fe (III) reducer and non-fermentative bacteria-isolated from municipal wastewater. A double chamber MFC was operated with three different electron donors including glucose, sucrose, and fructose. Substrate utilization pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Pseudomonas successfully used in MFCs is attributed to its great biodegradation capabilities [ 28 32 ], and it is considered to be an excellent anode biocatalyst [ 33 , 34 ]. However, the application of Pseudomonas as a bio-cathode in MFCs has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas successfully used in MFCs is attributed to its great biodegradation capabilities [ 28 32 ], and it is considered to be an excellent anode biocatalyst [ 33 , 34 ]. However, the application of Pseudomonas as a bio-cathode in MFCs has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ali et al exposed the efficiency of using the species Pseudomonas eruginosa, which generated 136 ± 87 mW/m 2 from the use of glucose, followed by fructose and sucrose. This study observed that the cell fed with glucose presented higher bacterial adhesion [66]. On the other hand, Acinetobacter bereziniae was identified as a Gram-negative, aerobic, non-fermentative, oxidase-negative, and immobile organism [67].…”
Section: Results and Analysismentioning
confidence: 99%
“…Microbial fuel cells (MFC) are devices that convert metabolic energy into electrical current using P. aeruginosa or other bacteria [ 170 ]. As a way of taking advantage of the metabolic potential of P. aeruginosa , the electric current can be generated using conventional substrates [ 171 ], and unconventional substrates, such as toluene, a toxic compound that is degraded by P. aeruginosa to produce electrical current [ 127 ]. Crude glycerol, a co-product of the process of obtaining biodiesel and the largest residue in this industrial sector, has also produced promising results [ 138 ].…”
Section: Pyocyanin Applications and Perspectivesmentioning
confidence: 99%